NEUROSPORA BIBLIOGRAPHY - Joseph C. Schmit (Fungal Genetics Reports, 1998)
Every attempt has been made to insure that the citations appear exactly as they do in the original publication. Entries for which the original could not be obtained for verification are indicated by (-).